2011
DOI: 10.1007/s11106-011-9304-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of sintered iron–boron–carbon alloys with different carbon contents

Abstract: The structure and mechanical and tribotechnical properties of iron-boron-carbon alloys produced from a mixture of iron, boron carbide, and graphite powders by single pressing and sintering are used to examine heterophase wear-resistant materials containing from 0.8 to 2.4% boron and from 0.7 to 1.6% fixed carbon. The wear resistance of the materials depends on the ratios of boron and carbon in them and on their total content and substantially exceeds the wear resistance of ShKh15 steel chosen as a reference sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Herewith, the significant capacities for manufacturing of low-alloy steels, which operational characteristic often are not inferior of the level of the same for steels, produced with application of traditional alloying modes, makes it possible the use of boron as basic alloying element (Dudrova, 1993;Gülsoy, 2004;Napara-Volgina, 2011;Suzuki, 2002). In our previous articles it has been demonstrated that boron addition to the base material is very efficient way for improving basic mechanical properties of sintered steels as well positive effect on activation of sintering was observed too.…”
Section: Introductionmentioning
confidence: 99%
“…Herewith, the significant capacities for manufacturing of low-alloy steels, which operational characteristic often are not inferior of the level of the same for steels, produced with application of traditional alloying modes, makes it possible the use of boron as basic alloying element (Dudrova, 1993;Gülsoy, 2004;Napara-Volgina, 2011;Suzuki, 2002). In our previous articles it has been demonstrated that boron addition to the base material is very efficient way for improving basic mechanical properties of sintered steels as well positive effect on activation of sintering was observed too.…”
Section: Introductionmentioning
confidence: 99%